Effects of the presence of insulated and non-insulated floating electrodes on side flashing - Nourirad, Ghasem; Gomes, Chandima; Izadi, Mahdi; Siow, Chun Lim; Ab Kadir, Mohd Zainal Abidin (IEEE, 2014)
Metallic part would play an influential role in the case of probability of lightning strikes. An experimental study has been done to find out the effect of the presence of floating electrode on the body during thunderstorm. Although, it is clear that a small metal part on the body or in vicinity does not have effect during direct strike, the effects has been examined only in the case of side flashing. SPSS has been used to check the statistical significance of the probability. According to the result, floating electrode may shorten the gap distance of the struck point and a human body thus increasing the probability of lightning side flashing. The test has been done covered floating electrode (insulated) as well. Thus, it is recommended to either remove or isolate the metal parts during thunderstorm.